Analyzing Malaysia's changing alignment choices, 1971-89 - Cheng Chwee, Kuik (Penerbit UKM, 2010)
This article analyzes Malaysia’s changing policies toward China and other big powers during the period 1971-1989, as a case to illustrate how and why smaller states adjust their alignment choices in the wake of reduced strategic commitment of their big power patrons the way they do. It argues that it was due to the changing distribution of regional power in the face of the British East of Suez policy and the American retreat from mainland Southeast Asia in the late 1960s – in conjunction with domestic political considerations in the post-1969 period – that had compelled Malaysia’s ruling elite to replace the country’s long-standing pro-West policy with a new posture of “non-alignment” and “regional neutralization”. In the view of the elite, in order to get the big powers to recognize and guarantee the region as an area of neutrality, the Southeast Asian states should acknowledge and accommodate each of the major powers’ “legitimate interests”, while observing a policy of “equidistance” with all the powers. This new alignment posture necessitated the Tun Razak government to adjust its China policy, paving way for the Malaysia-China rapprochement of the early 1970s.